Comments on Economic Models, Economics, and Economists: Remarks on Economics Rules by Dani Rodrik - Rubinstein, Ariel (Journal of Economic Literature, 2017)
This essay reviews Dani Rodrik's superb book Economics Rules and argues that it can serve as an ideal platform for discussing what economists can and should accomplish. The essay comments on some of the major issues in contemporary economics examined in the book: whether economics is a science, the meaning of economic models, the nature of “facts” in economics, and others. It also touches on issues that the book overlooks, such as the sociology of the profession, the teaching curriculum in economics, and the dismal situation of publishing in economics. (JEL A11, B40, C50)